Pengaruh Perbedaan Konsentrasi Pakan Pelet Terhadap Bobot Dan Panjang Ikan Mas (Cyprinus Carpio) - Muhammad Thoifur Fajar (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
Pellet feed is feed that is commonly used for the cultivation of livestock, namely broiler chickens, birds, hamsters, rabbits, fish and shrimp. Carp (Cyprinus carpio) is a fish that is often cultivated because it has economic opportunities and increasing demand. This study aims to determine the growth in length and weight of carp with pellet feeding. The research was conducted at the Basic Science Laboratory of UNARS campus 2 in July and August 2022. The method of observing the length and weight of carp using descriptive analysis method. The goldfish samples tested were 3 groups with 3 goldfish in each group. Groups of carp A, B and C were given different pellet feed treatments with pellet feed concentrations of 3%, 4% and 5% of the weight of the carp group. The results showed that pelleted feed with a concentration of 4% of carp B group added the highest weight of carp compared to feed with a concentration of 3% of carp A group and feed of 5% concentration of carp C group. The highest absolute length growth was seen in feed with 3% concentration of group A compared to feed with a concentration of 3% of group A. 4% concentration feed group B and 5% concentration feed group C